Stability of the effect of the stress-resistance-developmental programme on the formation of students' personal agency - Alexander V. Kaptsov; Inna L. Matasova; Maria A. Shatalina (Saratov State University, 2022)
Defining psychological and pedagogical conditions of students' personal agency development is still one of the challenging tasks of modern psychology. It is possible to consider the implementation of a developmental programme, which is aimed at the formation of students' stress resistance, as the solution to this problem. The developmental programme should be aimed at reducing maladaptive stress reactions and it should also contribute to the development of students' individual stress resisting strategy. The purpose of the research is to study the delayed eff ect of the developmental programme aimed at the formation of university students' stress resistance. In the course of a quasi-experimental study, the authors have proved the hypothesis of a delayed eff ect of the developmental programme. The essence of the programme is to prevent and to reduce maladaptive stress reactions that contribute to the development of an individual stress resisting strategy of students majoring in psychology and pedagogy. Psychological characteristics (21 subjects, M = 20.1 years old, Sd = 0.41) have been monitored before the implementation of the programme, after its completion and 4.5 months later. The authors used the following methods to diagnose psychological characteristics: Questionnaire on the stages of the students' personal agency development OSS-S4 (ОСС-С4) (A. V. Kaptsov, E. I. Kolesnikova), Questionnaire on the ways of performing learning actions OSS-SF3 (ОСС-СФ3) (A. V. Kaptsov, E. I. Kolesnikova), Emotional Creativity Questionnaire (R. J. Averill, adapted by T. V. Kornilova), Methodology of Life Orientations (SZhO) (D. A. Leontiev). The article presents the results of factorial and correlation analysis of diagnostic results. It also shows the effi ciency of students' personal agency development by increasing their emotional creativity. The authors claim that participation of students in the developmental programme which is aimed at the formation of their emotional self-regulation has had a positive eff ect on the structural changes in the system of the personal agency development stages. The research revealed short-term changes in the intra-system correlation between the stages of the personal agency development and the ways of performing learning actions. The applied aspect of the study is determined by identifi cation of the positive impact of the stress resistance development on the structural changes in the system of students' personal agency development stages.